HOME VISIT FOR APPLYING FAMILY NURSING: A PERSPECTIVE - Kusuma Wijaya Ridi Putra (Nurse and Health: Jurnal Keperawatan, 2019)
The paradigm shift from hospital-based care to community-based care lead role of health workers in Primary Health Care became an important part in improving public welfare through the field of health. A community nurse is required to be able to make approaches to the community, including conducting a home visit, in order to increase public awareness and concern for their health level.Keywords: Home visit, family empowering, family nursing